Zn, Fe, Se, and I concentrations present in tomato as affected by neem extract preservation in Sokoto, Nigeria - Yusuf (Journal of Tropical Chemistry Research and Education, 2023)
Nowadays addition of chemicals to save tomatoes against early spoilage is rampant, but the chemicals are harmful; thus, bio-based alternative with novel features are needed. The aim of this study was to discover the effect of using neem leaves extract for preservation of two tomato cultivars collected from Sokoto, Nigeria. 5%, 10% and 25% (w/v) aqueous solutions of neem extract to be used to coat tomatoes were prepared and an experiment was done in a randomized control trial. Consequently, with the addition of neem extract for preservation of tomato; Zn, Fe, Se, and I were assessed in Daneka tomato variety using atomic absorption spectrometry. The Fe level increase from 13.0 ± 0.05 ppm to 16.1 ±0.01 ppm. Selenium increase from 2.0 ± 0.05 ppm to 5.2 ± 1.5 ppm, iodine increase from 6.2 ± 0.02 to 8.0 ± 0.02 ppm in Daneka, and zinc increase from 14.0 ± 0.5 to 18.0 ± 0.2 ppm. The ranges of the determined Fe, Se, Zn, and I micronutrients in UTC tomato variety are respectively as follows: 14.0± 0.03 to 18.0± 0.03 ppm, 3.1± 0.03 to 7.0± 0.01 ppm, 15.6± 0.04 to 18.0± 0.01 ppm, and 7.0± 0.02 to 9.1± 0.02 ppm. Therewith, the concentrations of micronutrients increase with an increase in neem extract concentrations (p < 0.05). more studies are needed to make neem extract as a cheap, safe, and accessible substance for tomato preservation.